Redox degradable 3‐helix micelles with tunable sensitivity. Issue 1 (17th May 2019) - Xue, Yi; Jung, Benson T.; Xu, Ting
Abstract: We report a new design of redox‐responsive 15 nm 3‐helix micelles with tunable cargo release pathway. The self‐assembled micelles are structurally stabilized by the 3‐helix bundle forming peptide‐poly(ethylene glycol) conjugates and exhibit excellent stability without the presence of reducing agent (e.g., glutathione). Incorporating disulfide linkers at different locations of peptide‐poly(ethylene glycol) conjugates yields different redox‐degradation products that enable different degradation kinetics of the micelle and subsequently cargo release pathway. In conjunction with other attributes of the 3‐helix micelle such as small size, long circulation, and deep tumoral penetration, the present study provides an effective strategy toward controlled intercellular delivery of hydrophobic drugs and therapeutic peptides. Abstract :